Anticancer Activities of Polygonum odoratum Lour.: A Systematic Review - Khuayjarernpanishk, Thanut; Sookying, Sontaya; Duangjai, Acharaporn; Saokaew, Surasak; Sanbua, Asawadech; Bunteong, Orapa; Rungruangsri, Nutnicha; Suepsai, Witchuda; Sodsai, Patinya; Soylaiad, Jiraporn; Nacharoen, Varintorn; Noidamnoen, Suwanna; et al. (Frontiers in Pharmacology, 2022)
Cancers are a potential cause of death worldwide and represent a massive burden for healthcare systems. Treating cancers requires substantial resources, including skilled personnel, medications, instruments, and funds. Thus, developing cancer prevention and treatment measures is necessary for healthcare personnel and patients alike. Polygonum odoratum (Polygonaceae family) is a plant used as a culinary ingredient. It exhibits several pharmacological activities, such as antibacterial, antifungal, antioxidant, anti-inflammatory, and anticancer. Several classes of phytochemical constituents of P. odoratum have been reported. The important ones might be polyphenol and flavonoid derivatives. In this systematic review, the activities of P. odoratum against cancerous cells were determined and summarized. Data were obtained through a systematic search of electronic databases (EMBASE, PubMed, Scopus, Thai Thesis Database, Science Direct and Clinical Key). Eight studies met the eligibility criteria. The cancerous cell lines used in the studies were lymphoma, leukemia, oral, lung, breast, colon, and liver cancer cells. Based on this review, P. odoratum extracts significantly affected Epstein-Barr virus (EBV) genome-carrying human lymphoblastoid (Raji), mouse lymphocytic leukemia (P388), human acute lymphocytic leukemia (Jurkat), breast adenocarcinoma (MCF-7), human colon adenocarcinoma (HT-29), human T lymphoblast (MOLT-4), human promyelocytic leukemia cell line (HL-60), human hepatocellular carcinoma (HepG2), and oral squamous cell carcinoma (SAS, SCC-9, HSC-3) through induction of cell apoptosis, arrest of the cell cycle, inhibition of cell proliferation, migration, and colonization. The molecular mechanism of P. odoratum against cancers was reported to involve suppressing essential proteins required for cell proliferation, colonization, migration, apoptosis, and angiogenesis. They were survivin, cyclin-D, cyclooxygenase 2 (COX-2), matrix metalloproteinase-9 (MMP-9), and vascular endothelial growth factor A (VEGF-A). The extract of P. odoratum was also involved in the protein kinase B (Akt)/mammalian target of rapamycin (mTOR) pathway by inhibiting the expression of Akt, phosphorylated Akt, mTOR, and phosphorylated mTOR. From the key results of this review, P. odoratum is a promising chemotherapy and chemopreventive agent. Further investigation of its pharmacological activity and mechanism of action should be conducted using standardized extracts. In vivo experiments and clinical trials are required to confirm the anticancer activity.